2011
DOI: 10.1111/j.1399-3046.2011.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for oral human immunoglobulin in the treatment for norovirus enteritis in immunocompromised patients?

Abstract: No treatment for NVE is available. Immunocompromised patients with NVE treated with OHIG (12 cases) were retrospectively identified and matched 1:1 by age and gender with immunocompromised patients with NVE not treated with OHIG (12 controls). Chi-squared test, t-test, bivariate conditional linear regression analyses, and Kaplan-Meier curve were performed. A total of 58.3% patients were small bowel transplant (SBT) recipients. Although not statistically significant, cases compared with controls were more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 15 publications
1
63
0
Order By: Relevance
“…Florescu and colleagues performed a matched case-control study to evaluate the potential benefit of orally administered human immunoglobulin in the treatment of symptomatic norovirus infection in immunocompromised patients. Cases received 25 mg/kg of body weight of human immunoglobulin (Gamunex; Talecris Biotherapeutics, Inc., NC, USA) every 6 h for a total of 8 doses (58). Although the median age of 24 total cases plus controls was 2 years, one-third were adults, and 20 were solid organ transplant recipients.…”
Section: Management Of Norovirus Infectionmentioning
confidence: 99%
“…Florescu and colleagues performed a matched case-control study to evaluate the potential benefit of orally administered human immunoglobulin in the treatment of symptomatic norovirus infection in immunocompromised patients. Cases received 25 mg/kg of body weight of human immunoglobulin (Gamunex; Talecris Biotherapeutics, Inc., NC, USA) every 6 h for a total of 8 doses (58). Although the median age of 24 total cases plus controls was 2 years, one-third were adults, and 20 were solid organ transplant recipients.…”
Section: Management Of Norovirus Infectionmentioning
confidence: 99%
“…Several strategies have been tried in limited numbers of patients: oral or intravenous immunoglobulin, breast milk, ribavirin, and nitazoxanide. Several case series have suggested that oral human immunoglobulin improves diarrheal symptoms; however, a recent cohort study failed to demonstrate improvements in total time to resolution of diarrhea, length of hospital stay, or cost with administration of oral human immunoglobulin [40,53,62,63]. Systemic administration of immunoglobulin has also provided conflicting evidence on clinical impact [40].…”
Section: Norovirusmentioning
confidence: 99%
“…Norovirus may present in transplant recipients as severe or protracted diarrheal illness requiring admission to the hospital for supportive therapy, and may even cause recurrent or relapsing infection [139]. IT recipients usually present with severe diarrhea that requires prolonged intravenous fluid replacement and nutritional support, while vomiting is not a primary symptom [139][140][141].…”
Section: Norovirusmentioning
confidence: 99%